Factors associated with institutionalization of the elderly and the usefulness of elder day care centers in a District in Sri Lanka - Balasuriya, A (My University, 2001)
Reasons for the usefulness of elder day care centers for the elderly and their caregivers were mainly psychosocial and less financial. The elderly and their caregivers who utilized the services of elder day care centers cited psychosocial and not financial reasons for the perceived usefulness of these. Companionship and involvement in activities were the main reasons given by the elderly. Better mental well being of the elderly and the freedom enjoyed by the caregivers during daytime were the main reasons given by the care givers. The perceived needs of the elderly as given by the elderly and their care givers were mainly economic and health. Better accessibility to obtain medicine, getting them at a low cost and receiving subsidized living aids were the priority needs of the elderly. Needs of the elderly as perceived by the care givers were, monetary incentives to provide better care for the elderly, in addition to the above needs